A tutela penal da ordem tributária no estado democrático de direito - Barreto, Carlos Eduardo Gonzales (2012)
This master thesis has as purpose, given the current importance of tax collection in the national scenario, to analyze how this institute is tutored in Brazil by the criminal law and procedural criminal law. Thus, aiming at reaching this object, it was primarily performed a study of the history and characteristics of the Democratic Rule-Of-Law State, adopted in the Federal Constitution of 1988, of its supporting pillars, namely, the sovereignty, citizenship and the dignity of the human person and also the constitutional principles that guide the punitive power of the State. Thereafter, in an analysis on the advance of global criminality, which has as main figure the Economic Criminal Law, it was found that under the pretext of combating it, the society started to clamor for a more punitive State, which, consequently, leaded in certain moments to a reduction of the individual rights and guarantees. In Brazil, this reflex could be seen in the tax crimes, when the Judiciary allowed, as a manner of combating the tax criminality, the use of generic denounces. Still based on the purpose of this work, it is important to emphasize that the protection given by the Federal Constitution to the tax order about Brazil, which, in thesis would justify the application of the criminal and procedural criminal tutelage over this institute. To that end, a complete approach on the typical figures and the criminal procedure of the tax crimes provided in Law No. 8.137/90 is performed, and how these crimes are treated in countries like Portugal and Spain, which have a historic and cultural connection with Brazil. Finally, in spite of the Brazilian legislator using the criminal tutelage in the protection of the tax order, it is also verified that the great objective of the State in the criminal tax area is to ensure the tax collection. That premise may be proven before the history of laws that allowed, and still allow, the suspension or extinction of the punitive claim before the tax payment in installments or payment of the tax debt, respectively, which raises the discussion on the real necessity of criminalization of tax torts